2018
DOI: 10.1080/10586458.2018.1459962
|View full text |Cite
|
Sign up to set email alerts
|

How Many Eigenvalues of a Product of Truncated Orthogonal Matrices are Real?

Abstract: A truncation of a Haar distributed orthogonal random matrix gives rise to a matrix whose eigenvalues are either real or complex conjugate pairs, and are supported within the closed unit disk. This is also true for a product P m of m independent truncated orthogonal random matrices. One of most basic questions for such asymmetric matrices is to ask for the number of real eigenvalues. In this paper, we will exploit the fact that the eigenvalues of P m form a Pfaffian point process to obtain an explicit determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…As t grows, the eigenvalues increasingly concentrate on the real line. This concentration phenomenon has also been observed for products of other kinds of random matrices [31,32,33,34,35,36,37]. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…As t grows, the eigenvalues increasingly concentrate on the real line. This concentration phenomenon has also been observed for products of other kinds of random matrices [31,32,33,34,35,36,37]. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 69%
“…It is known that, for large N , real Ginibre matrices have a finite fraction of real eigenvalues (asymptotically 2N/π of them [30]). Moreover, a product of t such matrices has 2tN/π real eigenvalues [36], to leading order for large N and small t (this √ t growth is also true for a product of truncated orthogonal matrices [37]). Although we are more interested in small matrices, we have observed that something similar also happens in the context we are addressing.…”
Section: Spectrummentioning
confidence: 83%
“…Using this integrable structure, the probability that all eigenvalues of a product of truncated orthogonal random matrices are real was calculated in [20]. Simplified expressions for the correlation kernel of the Pfaffian point process were obtained in the recent work [19].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Õm form a Pfaffian point process [28]. In the recent work [19] this has been simplified and explicit formulae for the correlation kernel of the Pfaffian point process were identified. Theorem 2.1 (Forrester,Ipsen and Kumar [19]).…”
Section: Strategy Of the Proof And Leading Order Asymptoticsmentioning
confidence: 99%
See 1 more Smart Citation